2008
DOI: 10.1123/jsep.30.5.611
|View full text |Cite
|
Sign up to set email alerts
|

The CSGU: A Measure of Controllability, Stability, Globality, and Universality Attributions

Abstract: This article reports initial evidence of construct validity for a four-factor measure of attributions assessing the dimensions of controllability, stability, globality, and universality (the CSGU). In Study 1, using confirmatory factor analysis, factors were confirmed across least successful and most successful conditions. In Study 2, following less successful performances, correlations supported hypothesized relationships between subscales of the CSGU and subscales of the CDSII (McAuley, Duncan, & Russell, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Recently, Rees and colleagues (Coffee & Rees, 2008a, 2008b, 2011Coffee, Rees, & Haslam, 2009;Rees, 2007) have shown that, following success, efficacy beliefs increase when outcomes are attributed to causes that are perceived to generalise across time (stable) and/or situations (global) and/or are perceived as unique to the individual (personal); following failure, efficacy beliefs decrease when perceptions of uncontrollability are perceived to generalise across time and/or situations.…”
Section: Cognitive Consequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Rees and colleagues (Coffee & Rees, 2008a, 2008b, 2011Coffee, Rees, & Haslam, 2009;Rees, 2007) have shown that, following success, efficacy beliefs increase when outcomes are attributed to causes that are perceived to generalise across time (stable) and/or situations (global) and/or are perceived as unique to the individual (personal); following failure, efficacy beliefs decrease when perceptions of uncontrollability are perceived to generalise across time and/or situations.…”
Section: Cognitive Consequencesmentioning
confidence: 99%
“…To understand how team attributions influence behaviour patterns we recommend that researchers focus on four underlying dimensions: controllability, and three generalisability dimensions of stability, globality and universality. This conceptualisation enables researchers to explore how perceptions of controllability generalise across time (stability), situations (globality), and teams (universality), through going beyond the testing of main effects of attributions to exploring interactive effects of controllability and generalisability dimensions (Coffee & Rees, 2008a;Rees et al, 2005). Building upon the results of recent research (see Coffee, 2010, for a review), our main hypothesis is that main effects of generalisability dimensions have a greater role following team success; following team failure, main effects of controllability are important but they are conditioned by interactive effects for controllability and generalisability dimensions.…”
Section: Attribution Consequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, empirical evidence that links such attributions to subsequent performance is sparse. Instead, links are generally made between attributions and indices of behaviour, such as expectations for future success (e.g., Orbach, Singer, & Price, 1999; for a review see, Weiner, 1986), efficacy (e.g., Allen, Jones, & Sheffield, 2009;Bandura, 1997;Bond, Biddle, & Ntoumanis, 2001;Coffee & Rees, 2008, 2009Gernigon & Delloye, 2003), persistence (e.g., Le Foll, Rascle, & Higgins, 2006, learned helplessness (e.g., Alloy, Peterson, Abramson, & Seligman, 1984), and depression (e.g., Anderson, 1999). To address this gap in the literature, the present article reports the results of two experiments that examine the interactive effects of attributions for failure on self-efficacy and objective task performance.…”
Section: Introductionmentioning
confidence: 99%